2022
DOI: 10.1002/14651858.cd015291
|View full text |Cite
|
Sign up to set email alerts
|

Adults' views and experiences of vaccines developed in response to the COVID-19 pandemic: a qualitative evidence synthesis

Abstract: Adults' views and experiences of vaccines developed in response to the COVID-19 pandemic: a qualitative evidence synthesis (Protocol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Distrust has become a pervasive concept in the literature for understanding vaccine hesitancy and what drives it [ 37 , 42 ]. Like others, we have found that a major driver of vaccine hesitancy is people’s distrust in the experts, institutions, or systems implicated with vaccination, including for example scientists, the government, the state-run healthcare system, and the pharmaceutical industry [ 20 , 21 , 22 , 28 ]. This distrust emerged in our research as a significant determinant of vaccine hesitancy for various vaccines, amongst numerous populations and within many settings.…”
Section: Results: Overarching Reflective Insightssupporting
confidence: 63%
See 3 more Smart Citations
“…Distrust has become a pervasive concept in the literature for understanding vaccine hesitancy and what drives it [ 37 , 42 ]. Like others, we have found that a major driver of vaccine hesitancy is people’s distrust in the experts, institutions, or systems implicated with vaccination, including for example scientists, the government, the state-run healthcare system, and the pharmaceutical industry [ 20 , 21 , 22 , 28 ]. This distrust emerged in our research as a significant determinant of vaccine hesitancy for various vaccines, amongst numerous populations and within many settings.…”
Section: Results: Overarching Reflective Insightssupporting
confidence: 63%
“…For example, in our global and regional systematic reviews, we found that hesitancy towards HPV vaccination was uniquely connected to sociocultural norms surrounding adolescence, sexuality, and gender, and the values people attach to different sexual practices and sexualities [ 21 , 24 ]. Relatedly, it emerged from our research globally [ 22 ] and in South Africa [ 28 ] that COVID-19 vaccine hesitancy was often driven by concerns about the novelty of the vaccine and speed at which it was developed, which are concerns that did not emerge in the case of more routine vaccines that have been around for many years. Similarly, in our global systematic review, we found that the drivers of hesitancy towards routine childhood vaccines were potentially different for parents from higher and lower resource settings [ 20 ].…”
Section: Results: Overarching Reflective Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…From early on in the COVID-19 pandemic, vaccines, along with the wearing of face masks, social distancing, and advice around hand washing, were central public health interventions to control the spread of infection and contribute to achieving herd immunity and reducing the risk of severe illness [1]. During the pandemic, as new vaccines emerged, the WHO authorized a number of vaccines for emergency use globally, including Oxford-AstraZeneca, Johnson & Johnson, Pfizer-BioNTech, Moderna, Sputnik V, and Sinovac.…”
Section: Introductionmentioning
confidence: 99%